The influence of feeding strategies on trace element bioaccumulation in copepods (Calanoida). (March 2017) - Battuello, M.; Sartor, R. Mussat; Brizio, P.; Nurra, N.; Pessani, D.; Abete, M.C.; Squadrone, S.
Highlights: Trace elements levels were detected in Mediterranean calanoid copepods species. Feeding strategies are of great importance in metals bioaccumulation. Herbivorous copepods showed the highest BAFs and metals concentrations. The biodilution of most metal from herbivores to carnivores copepods was observed. Abstract: Copepods are the most numerous taxonomic group in marine mesozooplankton communities. These planktonic organisms have an essential role in the function of marine trophic webs, as they are the link between phytoplankton and secondary consumers. The concentrations of 20 essential and non-essential trace elements were investigated by Inductively Coupled Plasma – Mass Spectrometry (ICP-MS) in calanoid copepods with different feeding behaviors. The sampling was performed in the Northwestern Mediterranean Sea, at the border between the Northern Tyrrhenian Sea and the Ligurian Sea (Italy). Aluminum, iron, zinc and copper were present in the highest concentrations in herbivorous calanoids ( Temora stylifera, Nannocalanus minor, Neocalanus gracilis) . Conversely, the nonessential element – arsenic – and the essential elements selenium and molybdenum – were present in the highest levels in carnivores ( Pontella mediterranea, Candacia ethiopica). In the omnivorous copepod Centropages typicus, metal concentrations were found at an intermediate level between herbivores and carnivores, reflecting the importance of dietary pathways in metal intake and bioaccumulation. Finally, the bioaccumulation factors (BAFs), expressed as a ratio of the total metal levels in copepods compared to the seawater metal levels, were as follows: herbivores (83699) > omnivores (47855) > carnivores (41648).